Good Village Governance: Internal Control Model of Village Funds Management - Susilowati, Nurdian; Mahmud, Amir; Widhiastuti, Ratieh; Rahman- ingtyas, Wisudani (KnE Social Sciences, 2020)
This study aims to identify the activities and construct an internal control model of village funds management based on the Regulation of Ministry of Home Affairs No. 20 of 2018. The internal control model can be used to actualize good village governance. This study attempts to conduct in-depth interview to village officials and observation in Jambu District, Semarang. Based on the results of this study, the village funds management defines the activities as follows: (a) preparing the budget plan based on the programs set in Village Government Budget (APBDes) proposed as development, government, empowerment, and social activities; (b) carrying out the activities; (c) accountability; and (d) evaluation. Further, the fundamental components of internal control are control environment as the integrity and village officials’ ethics, the leadership of village chief, and the accountability. When village officials possess a strong integrity and ethics, frauds can be minimized. In the other hand, the financial statement is accountable. Besides, the democratic leadership of village chief can increase the accountability and communication so that the policy can be implemented properly as the objectives proposed. Furthermore, it is important to explore the role of society in internal control system of village funds management. Keywords: internal control, village funds management, good village governance